Identifying administrators' and faculty's perspectives regarding CAEP accreditation in a College of Education: A Q methodology research. (September 2021) - Alkhateeb, Hadeel; Romanowski, Michael H.
Highlights: Universities in the GCC region seek CAEP to provide legitimacy to their programs. Q methodology is used to examine faculty and administrators' perceptions regarding CAEP. Participants' perceptions differ regarding CAEP's advantages and disadvantages. Perceptions differ regarding CAEP's procedures and requirements. Perceptions differ regarding CAEP's impact on faculty and administrators' workload and agency. Abstract: In higher education, accreditation involves an external quality review process that scrutinizes universities, colleges, and educational programs to ensure that the education provided meets acceptable quality levels. Often considered the gold standard for institutions, the accreditation process originated in the US and quickly moved beyond American borders. Specifically, the Council for the Accreditation of Educator Preparation (CAEP) has moved to provide 'legitimacy' to universities in the Gulf Cooperation Council (GCC) region. Using Q methodology, this study examines faculty and administrators' perceptions regarding CAEP accreditation of a College of Education (CED) in the GCC. The results identify an apparent discrepancy among participants' perceptions regarding the CAEP accreditation's advantages and disadvantages, procedures and requirements, and impact on faculty and administrators' workload and agency.